Effect of Garnet Characteristics on Abrasive Waterjet Cutting of Hard Granite Rock - Tae-Min Oh; Gun-Wook Joo; Yohan Cha; Gye-Chun Cho (Advances in Civil Engineering)
Abrasive waterjet cutting technology has come back into use in the field of rock excavation (such as for tunneling) due to the need for precision construction with low vibration. Because the abrasive particles play an important role in efficient erosion during the cutting process, the abrasive characteristics strongly affect the rock cutting performance. In this study, rock cutting tests were performed with five different coarse (40 mesh) garnets to explore the effect of the abrasive feed rate, physical properties, and particle size distribution on rock cutting performance. In addition, garnet particle disintegration was investigated with garnet characteristics for the abrasive waterjet. The test results indicate that the particle size distribution, garnet purity, specific gravity, and hardness are the most important parameters for rock cutting performance. This study offers better understanding of coarse garnet performance and efficiency according to the garnet characteristics. This should provide assistance in selection of the garnet needed to achieve the desired performance for hard rock cutting.